ATTRACTING FACTORS FOR MIDDLE EAST STUDENTS IN MALAYSIA - Hamid, Junainah Abd; shukri, Sakinah mohd; Tham, Jacquline (International Journal of Psychosocial Rehabilitation, 2020)
The point of the examination is to distinguish significant powerful factors for pulling in Iranian vacationers in Malaysia, An exact examination. The travel industry is viewed as an industry which can be profoundly gainful for countries and it tends to be seen from a worldwide point of view. The consequences of the examination in Malaysia demonstrated that the picture of the nation which originates from positive verbal exchange has the most noteworthy effect on the Iranian vacationers. For the past few years, a lot of Iranians came to Malaysia to visit the country recommended by their friends, relatives and families who are in Malaysia to study, and by a lot of Iranians who came to study in Malaysia. Cultural similarities, being a Muslim country, friendliness and hospitality of the Malaysians and the good quality of the universities and education have led to positive words of mouth. Those who visited the country recommend that their friends and families visit the country and it has become a favourite destination for Iranian tourists.